Pengaruh Gaya Kepemimpinan Terhadap Kinerja Pegawai Pada Kantor Camat Panca Lautang Kabupaten Sidenreng Rappang - Ahmad Afif Basri; Gazali Amin; Mifta Farid Salam (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine the effect of Leadership Style on Employee Performance at the Panca Lautang Sub-district Office, Sidenreng Rappang Regency. This study uses a quantitative method with a descriptive approach. The population and sample of the study include all employees at the Panca Lautang Sub-district Office, with a sample determination technique using the saturated sample method. The data used consists of primary and secondary data. Primary data is obtained from questionnaires filled out by respondents, while secondary data is in the form of supporting research data. Data collection techniques include observation, documentation, interviews, and questionnaires. Data analysis is carried out through validity and reliability tests of research instruments, classical assumption tests (normality tests, heteroscedasticity tests, and linearity tests), simple regression analysis, and hypothesis testing including t-tests (partial) and coefficient of determination tests (R²). Hypothesis testing shows that the t-value of 3,341 is greater than the t-table of 1,701 with a significance value of 0.002 which is smaller than 0.05. This shows that Leadership Style (X) has a positive and significant influence on Employee Performance at the Panca Lautang Sub-district Office, Sidenreng Rappang Regency.